An analysis of the 1875-1877 scarlet fever epidemic of Cape Breton Island, Nova Scotia - Parish, Joseph MacLean, 1974- (University of Missouri--Columbia, 2004)
The entire dissertation/thesis text is included in the research.pdf file; the official abstract appears in the short.pdf file (which also appears in the research.pdf); a non-technical general description, or public abstract, appears in the public.pdf file. Title from title screen of research.pdf file viewed on (June 29, 2006) Includes bibliographical references. Vita. Thesis (Ph. D.) University of Missouri-Columbia 2004. Dissertations, Academic -- University of Missouri--Columbia -- Anthropology. An epidemic of scarlet fever on Cape Breton Island, Nova Scotia, Canada between 1875 and 1877 is analyzed in the context of a larger, world-wide pandemic of scarlet fever that occurred between 1825 and 1885. Data derived from public records on national censuses, provincial vital death records and parish records suggest that the epidemic impacted the two main ethnic groups of the island, the Acadians and the Scots, in very different ways. Statistical analysis was done considering the temporal and socio-cultural context of cause of death reporting in order to examine if this initial reading is valid. A deterministic computer model was also created to analyze the effects of each factor on the overall course of the epidemic. Results suggest that although the two groups did experience the epidemic in different ways, this difference is partially attributed to the terms used to describe cause of death information. Occupation, and household type resulting from occupation, is found to be a key indicator of epidemic experience. Differences in person to person contact rate are association with the different occupations/household types. Ethnic group preferences for the occupations of fishing or farming inextricably tie the issues of ethnicity and occupation together. The number of contacts people have per unit of time was found to be one of the major factors correlated to the epidemic experience. These results emphasize the importance of socio-cultural factors in an age where drug therapies are becoming less effective. ...